Simulation of ship seismic wave field in shallow sea based on three-dimensional staggered grid. (2018) - Zhu, Xufang; Yan, Bing
To find the law of ship seismic wave field in shallow sea, three-dimensional staggered grid method is adopted. Firstly, this algorithm is used to compare wave fields in the YOZ and XOZ planes, which shows that t characteristics of them are basically the same. Secondly, it is used to change source depth, which shows that the closer the source is near to the seabed, the stronger the surface wave in the wave field; the energy ratio near the focus in horizontal direction is the higher, while the vertical energy ratio is higher. The lower the centre frequency is, the stronger the surface wave signal. Last, the far-field law is observed, which shows that P wave and S wave merge into one wave group, the velocity is somewhere between them, and the surface waves still can be clearly observed due to slow attenuation.